2021
DOI: 10.1128/aem.00301-21
|View full text |Cite
|
Sign up to set email alerts
|

The Yeast eIF2 Kinase Gcn2 Facilitates H 2 O 2 -Mediated Feedback Inhibition of Both Protein Synthesis and Endoplasmic Reticulum Oxidative Folding during Recombinant Protein Production

Abstract: Recombinant protein production is a known source of oxidative stress. Knowledge of which ROS are involved or the specific growth phase in which stress occurs however remains lacking. Using modern, hypersensitive genetic H 2 O 2 -specific probes, micro-cultivation and continuous measurements in batch culture, we observed H 2 O 2 accumulation during and following the diauxic shift in engineered Saccharomyc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 67 publications
(114 reference statements)
0
6
0
Order By: Relevance
“…Although SIP-α(Δ55−70) and SIP-Ost1(Δ30−43) strains secreted more HRP, they still had significantly higher intracellular residues compared with the residue in the RAD14 strain (Figures 5C and 6A), activating the unfold protein response (UPR) and upregulating the expression of genes involved in protein folding and secretion. 22 The purified extracellular HRP was deglycosylated by Endo H and detected by SDS-PAGE to further confirm the increasing secretory amount of HRP during optimization (Figure S2). The titers of HRP were also calculated according to the volumetric activities in the supernatant and the specific activity of purified fermentation samples (Table S8).…”
Section: ■ Results and Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Although SIP-α(Δ55−70) and SIP-Ost1(Δ30−43) strains secreted more HRP, they still had significantly higher intracellular residues compared with the residue in the RAD14 strain (Figures 5C and 6A), activating the unfold protein response (UPR) and upregulating the expression of genes involved in protein folding and secretion. 22 The purified extracellular HRP was deglycosylated by Endo H and detected by SDS-PAGE to further confirm the increasing secretory amount of HRP during optimization (Figure S2). The titers of HRP were also calculated according to the volumetric activities in the supernatant and the specific activity of purified fermentation samples (Table S8).…”
Section: ■ Results and Discussionmentioning
confidence: 78%
“…To enhance the extracellular accumulation of HRP in S. cerevisiae, expression and secretory optimization of heterologous proteins have been regarded as two general but inevitable topics. , Due to the complex structure of HRP, the potential difficulty in protein folding is most likely to conflict with cell growth, , leading to the bottleneck when HRP was constitutively expressed in S. cerevisiae. , Meanwhile, HRP can cause cell stress in K.…”
Section: Introductionmentioning
confidence: 99%
“…However, upon stimulation, concentrations typically swiftly rise, allowing the second messengers to rapidly diffuse from their source to the ligand-specific protein sensors [89]. In this context, H 2 O 2 could be argued to perform a second messenger role in coordinating protein synthesis with, e.g., mitochondrial activity or ER-folding capacity [41,66]. Signal attenuation upon repeated stimulation (adaptation) is an inherent property of signaling systems involving adaptive changes in the equilibrium state of biological systems in response to alterations in their surrounding environment [90].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Gcn4 is neither activated by H 2 O 2 nor required for H 2 O 2 resistance in two other yeast strain backgrounds (S288c and CEN-PK) [65,66], suggesting that other Gcn2 targets may be more important in the ability of cells to adapt to H 2 O 2 in these strains. Interestingly, we recently showed that cells engineered to secrete increased levels of recombinant protein displayed increased levels of H 2 O 2 in the cytosol and Gcn2 activation [66]. Notably, Gcn2 deficiency restored H 2 O 2 levels, cytosolic protein synthesis and ER-folding homeostasis through an unknown mechanism, suggesting a role for H 2 O 2 and Gcn2 in balancing cytosolic protein synthesis to protein secretion in the ER.…”
Section: The Integrated Stress Responsementioning
confidence: 93%
See 1 more Smart Citation